Defective Pollen Wall 3 (DPW3), a novel alpha integrin‐like protein, is required for pollen wall formation in rice. Issue 2 (6th October 2019) - Mondol, Palash Chandra; Xu, Dawei; Duan, Lei; Shi, Jianxin; Wang, Canhua; Chen, Xiaofei; Chen, Mingjiao; Hu, Jianping; Liang, Wanqi; Zhang, Dabing
Summary: In flowering plants, pollen wall is a specialized extracellular cell‐wall matrix surrounding male gametophytes and acts as a natural protector of pollen grains against various environmental and biological stresses. The formation of pollen wall is a complex but well‐regulated process, which involves the action of many different genes. However, the genetic and molecular mechanisms underlying this process remain largely unknown. In this study, we isolated and characterized a novel rice male sterile mutant, defective pollen wall3 ( dpw3 ), which displays smaller and paler anthers with aborted pollen grains. DPW3 encodes a novel membrane‐associated alpha integrin‐like protein conserved in land plants. DPW3 is ubiquitously expressed in anther developmental stages and its protein is localized to the plasma membrane, endoplasmic reticulum (ER) and Golgi. Anthers of dpw3 plants exhibited unbalanced anther cuticular profile, abnormal Ubisch bodies, disrupted callose deposition, defective pollen wall formation such as abnormal microspore plasma membrane undulation and defective primexine formation, resulting in pollen abortion and complete male sterility. Our findings revealed a novel and vital role of alpha integrin‐like proteins in plant male reproduction.